Intriguing case of porokeratosis of mibelli on gluteal region - Snehal Balvant Lunge; Vijayalakshmi M Dhorigol; Anisha P Bindagi (Wolters Kluwer Medknow Publications, 2021)
Porokeratosis (PK) is a rare group of heterogeneous disorders of keratinization representing diverse phenotypic expressions of the same genetic defect, which is mainly inherited in an autosomal dominant manner. This report describes the case of a 40-year-old female with PK over the gluteal region. The rarity of this disorder, unusual site of presentation, and involvement of unilateral side of gluteal region, which is unusual in this form of PK, and the occurrence in a female patient motivated to report this case.